Burial practices in the early mid-Holocene of the Wallacean Islands: A sub-adult burial from Gua Makpan, Alor Island, Indonesia. (30th November 2021) - Samper Carro, Sofia C.; Stewart, Tahlia J.; Mahirta,; Wood, Rachel; O'Connor, Sue
Abstract: Mortuary contexts in geographical and chronological settings such as islands are key to investigating human migration pathways, population replacements, diet, health, occupational activities, belief systems as well as other aspects of social behaviour. Located between Mainland Southeast Asia and the Pacific, Island Southeast Asia is of particular interest in this respect. As yet, however, few complete burials predating the Neolithic have been recovered and described from within this vast region. This paper presents a sub-adult burial from Gua Makpan, Alor Island, Indonesia, which is dated to the early mid-Holocene. The anatomical description and bioskeletal profile of the remains is complemented by the analysis of mortuary practices. Our results suggest a delayed primary burial or a secondary treatment, where long bone diaphyses were removed prior to interment. The stratigraphical position of the remains indicates that the skeleton was not interred in anatomical position, which supports the hypothesis of secondary treatment of the remains. The mortuary practices documented in the sub-adult burial from Gua Makpan are compared to burial practices documented for sites from elsewhere in Island Southeast Asia. We assess differences and similarities in mortuary treatments, that could inform on shared mortuary rituals across this maritime region and changing social practices with human migrations, or the introduction of new burial practices.